Folic Acid–Conjugated Curcumin Nanoliposomes: A Targeted Delivery Platform with Enhanced Cytotoxicity and Sustained Drug Release in Breast Cancer Cells - Molavi Rahbar, Mohammad Kazem; Abassi, Mahsa; Motavaf, Forough; Boyqobilov, Soatmurod; Meliboev, Rozali; Sadikova, Gulchekhra; Mamatova, Malika; Islamova, Dilbar; Sabirova, Nadira; Keldiyorova, Zilola; Allahyartorkaman, Mohammadreza (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Breast cancer remains one of the most prevalent and fatal malignancies among women, emphasizing the need for safer and more effective therapeutic approaches. Curcumin is a multifunctional natural compound with proven anticancer activity; however, its low solubility and rapid systemic elimination restrict its clinical application. In this study, folic acid–linked PEGylated nanoliposomes (FA-Lipo-Cur) were developed to enhance curcumin delivery and cellular uptake in folate receptor–overexpressing MDA-MB-231 breast cancer cells. Materials and Methods: Curcumin-loaded, folate-conjugated nanoliposomes were fabricated via the thin-film hydration method followed by post-insertion of DSPE-PEG (3350)-FA. The formulations were characterized for particle size, ζ-potential, polydispersity index (PDI), morphology (SEM/TEM), encapsulation efficiency (EE%), and in-vitro drug release kinetics. Cytotoxicity was assessed using the MTT assay after 48 h exposure to FA-Lipo-Cur, non-targeted Lipo-Cur, and free curcumin. Results: Both formulations produced spherical vesicles with uniform morphology and high encapsulation efficiency (>75%). The mean particle size of FA-Lipo-Cur was 250 ± 7.7 nm, with a ζ-potential of −25.1 ± 2.1 mV and PDI of 0.16 ± 0.02, indicating excellent colloidal stability and homogeneity. In-vitro release studies demonstrated sustained curcumin release over 48 h, with a slower release rate for FA-Lipo-Cur compared to Lipo-Cur, attributed to steric stabilization by the PEG–folate corona. In cytotoxicity assays, FA-Lipo-Cur exhibited the lowest IC₅₀ (33 ± 3.3 µg/mL) compared with Lipo-Cur (45 ± 3.9 µg/mL) and free curcumin (55 ± 4.1 µg/mL) (p < 0.05). When folate receptors were pre-saturated with free folic acid, the IC₅₀ of FA-Lipo-Cur increased to 47.5 ± 3.2 µg/mL, confirming that enhanced cytotoxicity arose primarily from receptor-specific targeting rather than non-specific uptake. Conclusion: The FA-Lipo-Cur system therefore represents a promising, biocompatible nanocarrier platform for targeted breast cancer therapy, warranting further pharmacokinetic and in-vivo tumor model evaluation.